2010
DOI: 10.1051/0004-6361/200913665
|View full text |Cite
|
Sign up to set email alerts
|

Rotation measures of radio sources in hot galaxy clusters

Abstract: Aims. The goal of this work is to investigate the Faraday rotation measure (RM) of radio galaxies in hot galaxy clusters in order to establish a possible connection between the magnetic field strength and the gas temperature of the intracluster medium. Methods. We performed Very Large Array observations at 3.6 cm and 6 cm of two radio galaxies located in A401 and Ophiuchus, a radio galaxy in A2142, and a radio galaxy located in the background of A2065. All these galaxy clusters are characterized by high temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
96
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 90 publications
20
96
1
Order By: Relevance
“…On the other hand, no correlation seems to be present between the central magnetic field and the mean cluster temperature, in agreement with what found by Govoni et al (2010) in a statistical analysis of a sample of RM in rich galaxy clusters.…”
Section: D Simulationssupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, no correlation seems to be present between the central magnetic field and the mean cluster temperature, in agreement with what found by Govoni et al (2010) in a statistical analysis of a sample of RM in rich galaxy clusters.…”
Section: D Simulationssupporting
confidence: 89%
“…NGC 6251, 3C 449, NGC 383, (Perley et al 1984, but are much smaller in amplitude than in rich galaxy clusters (e.g. Govoni et al 2010). …”
Section: Polarization Results Summarymentioning
confidence: 89%
“…We further assume that the detected depolarization occurrs in the ICM, meaning neither eventual depolarization internal to the radio-sources nor in their immediate surroundings yield a dominant contribution (see Govoni et al 2006;Laing et al 2008;Bonafede et al 2010;Govoni et al 2010). The observed trend indicates that magnetic fields are common constituents of galaxy clusters, in agreement with the results by Clarke (2004) and Johnston-Hollitt et al (2004), who analyzed the Faraday rotation measures of sources located behind and within clusters.…”
Section: Fractional Polarization Trendsupporting
confidence: 84%
“…For example, magnetic fields of several μG were inferred in clusters without radio halo by e.g. Clarke et al (2001), and Murgia et al (2004), and recently, Govoni et al (2010) found that clusters seem to follow a common S X − RM distribution, S X being the X-ray surface brightness, independently on their radio properties. However, this is the first time that a statistical comparison between magnetic fields in clusters with and without radio emission has been performed and our result is a further indication that hadronic models are difficult to reconcile with present data (Brunetti et al 2008;and Dallacasa et al 2009;Donnert et al 2010;Jeltema & Profumo 2010).…”
Section: Magnetic Field and Radio Halo Originmentioning
confidence: 99%
See 1 more Smart Citation